Frekuensi Penggunaan Smartphone pada Siswa Kelas V Sekolah Dasar - Ditya Yushartina (PT Hakhara Akademia Indonesia, 2025)
The use of smartphones among elementary school students has increased significantly along with technological advancements and changes in learning patterns after the Covid-19 pandemic. Smartphones are not only used for entertainment but are also beginning to be utilized as learning tools. This study aims to describe the frequency of smartphone use among fifth-grade students at SDN 163 Pekanbaru, as well as to identify the purposes and time patterns of smartphone usage in students’ daily lives. This study employed a descriptive method with a quantitative approach. The participants consisted of 24 fifth-grade students at SDN 163 Pekanbaru. Data were collected through a questionnaire covering the duration of smartphone use, purposes of use, and time of use. The collected data were analyzed using frequency, percentage, and distribution calculations, and then described narratively. The results show that most students use smartphones for one to two hours per day, indicating a moderate level of usage. However, some students use smartphones for more than two hours per day. Smartphones are mainly used for entertainment activities, such as playing games and watching videos, although their use for learning purposes has also begun to emerge. In terms of time, smartphone use mostly occurs in the afternoon and evening. The study concludes that smartphone use among fifth-grade students needs proper supervision and guidance from teachers and parents to ensure that its use remains controlled and supports positive learning outcomes without negatively affecting students’ development.